Pengembangan E-LKPD Berbasis Inkuiri Terbimbing Menggunakan Aplikasi Adobe Acrobat 11 Pro Extended Materi Kesetimbangan Kimia - anggi kusuma Sari; Herdini Herdini; Susilawati Susilawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT This study aims to produce a Guided Inquiry-Based E-LKPD using the adobe acrobat 11 pro extended application on the chemical equilibrium material developed which is already valid based on aspects of content feasibility, pedagogics, characteristics of the guided inquiry model, language and graphic aspects. The type of research used is research and development using the ADDIE model. The results of material validation from each aspect are as follows, the content feasibility aspect is 92.18%, the pedagogic aspect is 90%, the characteristic aspect of the guided inquiry learning model is 87.5%, the language aspect is 90.62% and the graphic aspect is 93.75% with valid category. The results of media validation from each aspect are as follows, the size aspect of the E-LKPD is 93.75%, the cover design aspect of the E-LKPD is 90.62% and the content design of the E-LKPD is 93.18%. The results of the one-on-one test analysis show that students with high, medium and low abilities have a fast to long time span according to their abilities. The results of the teacher's response obtained a value of 93.55% with attractiveness 95.83%, effectiveness 93.18% and practicality 91.66% with good criteria. Student responses obtained a value of 91.5% with an attractiveness of 92.12% and an ease of 90.75% with good criteria.